Advances in data mining. Applications and theoretical aspects : 12th Industrial conference, ICDM 2012, Berlin, Germany, July 13-20, 2012. Proceedings - Perner, Petra (Lecture Notes in Computer Science, 2012)
This book constitutes the refereed proceedings of the 12th Industrial Conference on Data Mining, ICDM 2012, held in Berlin, Germany in July 2012. The 22 revised full papers presented were carefully reviewed and selected from 97 submissions. The papers are organized in topical sections on data mining in medicine and biology; data mining for energy industry; data mining in traffic and logistic; data mining in telecommunication; data mining in engineering; theory in data mining; theory in data mining: clustering; theory in data mining: association rule mining and decision rule mining.